Hemiparasitic features and antioxidant activity of Dendrophthoe pentandra and Scurrula atropurpurea on Diospyros rhodocalyx - NONTHIWAT TAESUK; SIRITHIDA BOONPEN; KULLASATREE MANEE; PASAKORN BUNCHALEE; TEERAPORN KATISART; VACHIRAPORN PIKULTHONG; SUTHIRA MANEECHAI (Society for Indonesian Biodiversity, 2025)
Abstract. Taesuk N, Boonpen S, Manee K, Bunchalee P, Katisart T, Pikulthong V, Maneechai S. 2025. Hemiparasitic features and antioxidant activity of Dendrophthoe pentandra and Scurrula atropurpurea on Diospyros rhodocalyx. Biodiversitas 26: 2531-2539. Mistletoe, a hemiparasitic plant, exhibits broad ecological adaptability, establishing parasitic relationships with a wide range of host species across diverse habitats and environmental conditions. Dendrophthoe pentandra and Scurrula atropurpurea, belonging to the family Loranthaceae, represent prominent hemiparasitic species with ecological and phytochemical significance. This study investigated the characteristics and phytochemical composition of mistletoe species growing on shared host trees. The phenolic and flavonoid contents, as well as the antioxidant activities (DPPH and ABTS assays) of these two hemiparasitic mistletoe species were examined in relation to their common host plant, Diospyros rhodocalyx. Comparative distribution analysis revealed that D. pentandra was more widely distributed across host trees than S. atropurpurea. Morphological assessments of reproductive structures indicated that D. pentandra produced larger and more vividly colored flowers and fruits compared to S. atropurpurea. The phytochemical profiles, total phenolic and flavonoid contents, and antioxidant activities of the leaf and stem extracts were investigated using different extraction solvents. Crude extracts were prepared by Soxhlet extraction with dichloromethane, ethanol, and ethyl acetate. The ethanol extract of D. pentandra stems provided the highest total phenolic content as determined by the Folin-Ciocalteu method. Antioxidant activities were assessed using the DPPH and ABTS assays, with the ethyl acetate extract of the stem from S. atropurpurea showing the highest antioxidant activity at IC50 values of 0.282±0.005 and 0.483±0.041 µg/mL, respectively. These findings provide insights into the ecological interactions between flower and fruit characteristics, chemical profiles, and potential bioactivities of mistletoe species.